Familia, prácticas empresarias y poder político. Un estudio comparado de los casos de Felipe y Manuel Posse en el contexto agroindustrial azucarero tucumano, 1830–1890 - Bolsi, Francisco (2012)
Since the beginning of sugar activity in Argentina, historians have controversially discussed their development. The focus in the dispute revolved around the necessity or appropriateness of protection and encouragement to those regionally localized and tax industries of domestic policies. Studying and researching the characteristics of the Posse clan members became an ideal instrument for analysing economic developments in sugar factories from the moment of its Foundation, the investments, the modernisation of the machinery, the reactions of family environment before the closure of the factories and the link between this process and the political stance of the Posse at local level.